Air concentration and bulked flow along a curved, converging stepped chute - Biethman, Blake W., author; Ettema, Robert, advisor; Thornton, Christopher, advisor; Wohl, Ellen, committee member (Colorado State University. Libraries, 2020)
This thesis focuses on the air-entrainment performance of a stepped spillway of unique form. The performance was determined using a hydraulic model constructed at a length scale (prototype length/model length) of 24. The new stepped spillway is part of the Gross Reservoir Expansion (GRE) project, which by 2025 is expected to raise the existing Gross Dam about a third of its current height. The stepped spillway will be the tallest stepped spillway in the United States. The model spillway consisted of a chute whose step dimensions, vertical to horizontal, were 0.051 m by 0.025 m, resulting in a chute slope (V:H) of 2.0 and a chute angle of 63.4°. Additionally, the chute conformed, in planform, to the curved planform of raised Gross Dam. At the spillway's crest, that radius of curvature, at model scale, was 22.2 m. The chute width converged by about 20% from the top of the chute to the stilling basin at the base of the chute. The chute's steepness, height, curvature and convergence made the chute's geometry unique among existing stepped spillways. The evaluation involved measurements of air entrainment and flow velocity along the stepped chute, for which the skimming flow regime prevailed for discharge larger than about 9% of the spillway's design discharge. To date, the effect on water flow and air entrainment of chute curvature in stepped spillways had not been investigated. The investigation was facilitated from measurements obtained using a dual-tip conductivity probe, which detected the instantaneous void fraction of the air-water mixture. The probe also enabled measurement of the velocity of the bulked flow along the chute. The study showed that, when the chute conveyed the design discharge (at model scale, 0.347 m3/s), streamwise values of air concentration and flow depth (bulked with entrained air) were basically constant near the bottom of the chute. Additionally, the chute's planform curvature resulted in non-uniform flow across the chute. At the design discharge, and near the bottom of the chute, the flow depth along the chute's centerline was nominally about 30% greater than the flow depth at the sidewall. When the chute's curvature was accounted for, the water surface along the centerline of the chute was approximately level with the water surface near the sidewall. Further, the depth-averaged concentration of entrained air near the bottom of the chute decreased with increasing water discharge. The chute's converging sidewalls mildly affected the flow near the sidewalls, causing slight increases in flow depth and reductions in flow velocity. These changes, though noticeable, were negligible in terms of spillway performance because of their magnitude.
Keywords: bulked flow; converging; stepped chute; conductivity probe; air concentration; curved